The Academic Achievement of Limited English Proficient (LEP) Youth in New and Established Immigrant States: Lessons from the National Assessment of Educational Progress (NAEP) - Spees, Lisa P. (Educ Policy Anal Arch, 2016)
The dramatic growth and dispersal of immigrant families has changed the face of public education at a time when states are experiencing increased school accountability pressures under the No Child Left Behind (NCLB) and its recent successor the Every Student Succeeds Act. Of particular concern is how these demographic shifts affect the academic well-being of Limited English Proficient (LEP) youth, the protected sub-group that most directly targets children from immigrant families. Using individual-level data from the National Association of Educational Progress, we examine how 8th grade test scores of LEP youth differ across new and established immigrant destination states. Results show that achievement for LEP youth is higher in new than in established immigrant states but that this advantage is not consistent across ethnic/racial groups. LEP youth in new immigrant states benefit from more favorable demographic characteristics and more family and school resources, but these differences only explain a small portion of the achievement gap.